The application of IAS 39 reclassifications by global systemically important banks (G-SIBs) since 2008/2009 - Modimakwane, Winnie Tebogo (Department of Finance and Tax, 2021)
The International Accounting Standard Board (IASB) introduced an amendment to the International Accounting Standard 39 – Financial Instruments: Recognition and Measurement (IAS 39) and to International Financial Reporting Standard 7 – Financial Instruments: Disclosures (IFRS 7) on 13 October 2008. These amendments allowed entities to reclassify non-derivative financial assets from the fair value option to historical cost. The purpose of this study is to explore how Global Systemically Important Banks (G-SIBs) applied the amendment to IAS 39 since 2008/2009. The study is guided by four main objectives in which the first two objectives explores how the G-SIBs applied the reclassifications during the allowed period, 2008/2009 and the period beyond 2009 when the application of the standard should have been stopped. The study further investigates if any G-SIBs used restatements to circumvent the requirements of the IAS 39 that does not allow reclassifications into and out of the ‘designated as at fair value' category. Finally, the study explores the impacts of the reclassifications on the G-SIBs' ROE and total regulatory capital with the aim to determine if G-SIBs reaped any long-term benefits from the reclassifications and whether any traces of earning and capital management exist in the way G-SIBs applied the amendment to IAS 39. To achieve these objectives a comparative case study approach, which is qualitative in nature/scope was used with 10 G-SIBS forming part of the units of the analysis of the study. The study finds that: (i) 70 percent of G-SIBs reclassified assets during 2008/2009; (ii) a significant improvement on the reported net income was observed with a slight improvement on the return on equity and regulatory capital during 2008/2009, while the long-term impacts on ROE and total capital are insignificant; and (iii) G-SIBs did not restate comparative figures to evade the prohibition on reclassifications into and out of the ‘designated as at fair value' category. As far as can be reasonably established, this kind of study has not been published before for G-SIBs. As such, the study contributes by including the analysis of G-SIBs and the long-term implications of applying the amendment to IAS 39 to the current literature, as well as adding another possible type of a restatement to the financial restatements' literature. All these aspects are currently lacking in the existing literature.